Being out of place: Non-belonging and queer racialization in the U.K - DasGupta, Debanuj; Dasgupta, Rohit K. (Emotion, space and society, 2018)
The question of refugee rights and immigrant entry to the UK presently has come under attack with the rise of nationalist sentiment and the exit of the UK from the European Union. The figure of the Muslim migrant has been normatively constructed to represent a limit to UK's multiculturalism (and, arguably globally). Such anti-Muslim sentiment operates via displacing racialized bodies from UK public culture. This article situates the ways in which racialized queer Muslim subjects attempt to maneuver structural racism and heteronormativity in the UK. The article argues that queer Muslim immigrants perceive queer spaces in Central London as white spaces. Secondly, we will analyze how the racialized queer Muslim subject creates ethno-racial specific spaces that are located outside central London. We argue that queer migration needs to be understood as an embodied experience by paying attention to how racialized queer Muslim migrants moves through multiple spaces in the city. The article develops a mixed method approach through an analysis of Ian Iqbal Rashid's film A Touch of Pink (2004) alongside Raisa Kabir's recent exhibition In/Visible Space: Reflections on the Realm of Dimensional Affect, Space and the Queer Racialised Self (Rich Mix, April, 2013) and the narrative of a gay identified working class Muslim immigrant male from East London. We argue that queer Muslim migrants reside on the margins of British symbolic culture through a non-belonging to one's religious identity. Such non-belonging is a spatialized experience. An analysis of the film, exhibition and our ethnography reveals the ways in which sexuality is constructed and conferred through racialization and creates precariously situated queer Muslim migrant subjects within present day UK. •Queer Muslim migration is an embodied affective experience.•Queer space is constituted through racialised processes which have long histories of colonial movement of capital.•Queer Muslims can create queer spaces within ethnic enclaves rather than through assimilation with mainstream queer cultures.•Article challenges attitudes which sees queer sexuality incompatible with racial/ethnic and religious identity.